PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT MARUWA INDONESIA - Sunarti Simarmata; Wasiman Wasiman (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This article aims to determine and analyze the effect of work environment and work discipline on employee performance at PT Maruwa Indonesia. The population in this study found 105 employees. The sample in this study used a saturated sample technique consisting of 105 respondents. The framework of this research consists of independent variables, namely work environment and work discipline, and the dependent variable, namely employee performance. This type of research uses quantitative methods and the data used are primary and secondary data obtained from the distribution of questionnaires and a list of statements whose measurements use a Likert scale. And all the data collected were analyzed using SPSS version 25. Data were analyzed using validity and reliability tests, classical assumption test in this study used normality test, multicollinearity test and heteroscedasticity test, influence test in this study used multiple regression analysis and analysis of the coefficient of determination (R2), while the hypothesis test in this study uses the T test and F test. The results of the T test show that the work environment has a significant effect on employee performance, work discipline has a significant effect on employee performance and. The results of the F test show that the work environment and work discipline simultaneously have a significant effect on employee performance.